Regulation of Food Intake in Adults with and without Obesity: The Role of the Gastrointestinal Tract and Gut-Brain Axis - Althubeati, Sarah (2024)
Obesity is a complex global health issue affecting a significant portion of the population. In the UK, it is estimated that approximately 1 in 4 adults and 1 in 5 children aged 10 to 11 years are living with obesity. Impairment in food intake regulation, including hunger and satiety sensations, are key factors contributing to overeating and weight gain, particularly in individuals with obesity. While various mechanisms may explain these alterations, such as altered appetite and satiety regulators, accelerated gastric emptying (GE), and heightened brain responses to food cues and reward, it remains inconclusive whether these mechanisms are altered in people living with obesity compared to normalweight (NW) adults.